The Question of Christian Community Online: The Case of the 'Artist World Network'. - Campbell, Heidi; Calderon, Patricia (Studies in World Christianity, 2007)
The article presents a study which investigates the constitution of an online Christian community. It explores a particular Christian online bulletin board called "Artist World Network" to examine how Christian communities function. The authors consider the possible challenges that the online Christian communities pose to the traditional Christian community.